The Ambulance: Toward a Labor Theory of Poverty Governance - Seim, Josh (American Sociological Review, 2017)
This article reimagines poverty governance as a labor process. Extending theories of bureaucratic fields and street-level bureaucracies, the proposed model suggests that the state manages the poor through fragmented activities embedded in horizontal and vertical relations of production. I use an ethnography of 911 ambulance operations in a single California county to advance this perspective. From plugging gunshot wounds to moving sidewalk slumberers, ambulance crews interact with a mostly impoverished clientele base by transforming spaces in bodies and bodies in spaces. This two-sided governance puts the ambulance in recurrent contact with the hospital emergency department and the police squad car. Across these institutions, ambulance crews struggle with their nurse and police counterparts over the horizontal shuffling of burdensome work, shaping the life chances of their subjects in the process. At the same time, bureaucratic and capitalistic forces from above activate a lean ambulance fleet that is minimally wasteful and highly flexible. This verticality structures clientele processing through the ambulance and fuels tensions across the frontlines of governance. In an effort to advance theory and fill an empirical gap, this article proposes a new model for understanding the management of marginality and highlights an overlooked case of poverty regulation.